Facilitating reflective practice via Instant Messenger Cooperative Development - Andrew Boon (Indonesian JELT, 2019)
Reflective practice may be considered an important part of the teaching process. By reflecting on their action, teachers can continually examine their classroom teaching and embrace possibilities for professional growth and change. This article describes how teachers can utilize Instant Messenger Cooperative Development (IMCD) (Boon, 2005, 2007, 2011, 2015); an online framework for reflecting on pedagogical practice. To illustrate IMCD in action, it examines a session in which a teacher explores ways for her learners to recycle and review language learned in previous lessons. The article then discusses the benefits of IMCD as an aid for reflecting on and finding workable solutions to pedagogic puzzles with the hope that readers of the article may go on to utilize IMCD for their own reflective practice purposes.